Personal perspectives a guide to decision making - Paolucci, Beatrice; Faiola-Priest, Theodora; Thompson, Patricia J. (New York Webster Division, McGraw-Hill, 1978)
A senior high school home economics text which focuses on decision making.
Includes index.
Keywords: Home economics -- Decision making; Home economics